TINJAUAN LITERATUR TENTANG GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI DALAM PEMBENTUKAN PERILAKU KERJA KARYAWAN DI PT. CEMINDO GEMILANG (CILEGON-BANTEN) - Vera Maria; Syaeful Hidayat; Anggi Qomala Sari; Geshyta Firda Zahra; Milla Nadrotul Aini; Andini Susanti (CV. Denasya Smart Publisher, 2025)
Employee work behavior is an important component to achieve organizational goals and performance. Transformational leadership style and organizational culture affect work behavior, but previous research results show different opinions. Therefore, this study aims to review and analyze the relationship between transformational leadership style and organizational culture on employee work behavior by examining previous research findings with relevant theories. The research method used in this study is a qualitative method that focuses on literature studies. This study uses articles by Zaenal Arifin, Wawan Prahiawan, and Ranthy Pancasasti to be analyzed as well as the basis for the research conducted. The purpose of this qualitative study is to understand how transformational leadership style and organizational culture have an influence on the formation of work behavior of PT. Cemindo Gemilang employees. The findings of this study indicate that the combination of leaders who have an effective leadership style and a strong organizational culture encourages employees to have productive work behavior. From this study, it is hoped that the company can foster leaders to be inspiring and have a healthy organizational culture.